(untitled) (Biodiversitas Journal of Biological Diversity, 2022)
Abstract. Sofiah S, Hakim L, Indriyani S, Robiansyah I. 2022. Acclimation study of Smilax nageliana A.DC., a climber species endemic to East Java, Indonesia. Biodiversitas 23: 4082-4089. Smilax L. species, popularly known in Indonesia as Canar, belong to the family Smilacaceae and have been used in folk medicine as a tonic against rheumatism and as anti-syphilitic. Smilax nageliana A.DC is an endemic plant to East Java, Indonesia which is only distributed in Ranu Darungan, Bromo Tengger Semeru National Park (BTSNP), and Mt. Kawi. In the effort for its conservation and sustainable management, information regarding the adaptation of S. nageliana to a new environment is necessary. The aim of this study was to investigate the acclimation of S. nageliana under three different treatments, namely (i) in hood application in a greenhouse; (ii) in its natural habitat under shade; (iii) in natural habitat in the open area. Each treatment had ten replications. Survival and growth performance were observed for six months in terms of survival rates, number of new shoots, shoot length, number of leaves and chlorophyll content. Environment factors were also measured including solar intensity, temperature, humidity and water content. Data were analyzed using a two-way Anova. The principal component analysis (PCA) was performed to determine the relationships between environmental components and S. nageliana acclimation performance. The result showed that S. nageliana had a one hundred percent survival rate in the hood application and natural habitat with shade. The best growth performances (i.e., shoot length, the number of leaves, shoots per root and chlorophyll content) were achieved under the hood application. The average temperature was quite influential on the first component (PC1), followed by solar intensity while water affected the second component (PC2). The findings of this study suggest that where sunlight/solar intensity and humidity were controlled, it gave the most optimal results for acclimation of S. nageliana.